Antimicrobial Peptides Secreted From Human Cryopreserved Viable Amniotic Membrane Contribute to its Antibacterial Activity. Issue 1 (December 2017) - Mao, Yong; Hoffman, Tyler; Singh-Varma, Anya; Duan-Arnold, Yi; Moorman, Matthew; Danilkovitch, Alla; Kohn, Joachim
Abstract Chronic wounds remain a large problem in the field of medicine and are often associated with risk of infection and amputation. Recently, a commercially available human cryopreserved viable amniotic membrane (hCVAM) has been shown to effectively promote wound closure and reduce wound-related infections. A sprevious study indicates that hCVAM can inhibit the growth of bacteria associated with chronic wounds. In the present study, we investigated the mechanism of hCVAM antimicrobial activity. Our data demonstrate that antimicrobial activities against common pathogens in chronic wounds such asP .aeruginosa, S .aureus and Methicillin-resistantS .aureus (MRSA) are mediated via the secretion of soluble factors by viable cells in hCVAM and that these factors are proteins in nature. Further, we show that genes for antimicrobial peptides (AMPs) including human beta-defensins (HBDs) are expressed by hCVAM and that expression levels positively correlate with antimicrobial activity of hCVAM. At the protein level, our data indicate that HBD2 and HBD3 are secreted by hCVAM and directly contribute to its activity againstP .aeruginosa . These data provide evidence that soluble factors including AMPs are hCVAM antimicrobial agents and are consistent with a role for AMPs in mediating antimicrobial properties of the membrane.